Penerapan Algoritma Regresi Linear Sederhana Untuk Prediksi Pengaruh Nilai Omset Terhadap Besaran Pendapatan Bersih Usaha Mikro Kecil Dan Menengah - ifan (E-Jurnal Universitas Samudra, 2023)
Micro, small and medium enterprises (MSMEs) are one of the business fields that can develop and be consistent in the national economy. Micro, small and medium enterprises (MSMEs) are good forums for job creation, which are planned by the government, private sector and individual business actors. The purpose of this study is to predict the increase in net income of micro, small and medium enterprises that affect the economic growth of Cilegon City. In this study using quantitative methods, namely analyzing and interpreting the relationship between variables through accurate and up-to-date data according to the problems in this study. The research method is carried out by examining data from data that is wrong or can interfere with the analysis process, performs analysis on the dataset and divides the data into training data and test data. The process of data sharing is 80% used for training data and 20% for test data. All processes are processed using Python programming. Python libraries used are numpy, pandas, matplotlib, seaborn, sklearn. The analysis process is done with Kaggel Notebook. The results of the study resulted in a simple linear regression model y = - 374359.94312876 + (0.20259073 (X)) with a Correlation value: 0.9999546662293942 Coefficient of determination 0.7244150380582826, Mean Absolute Error: 243269.23966642626, Mean Squared Error: 71893932500.72606 and 934012073. The final result of the analysis is a comparison between the actual y and the predicted y in the form of tables and graphs.